Mediastinitis in pediatric cardiac surgery: an unusual complication. A single-center experience - Manosalva Arciniegas, Laura Isabel (2025)
Objectives. Mediastinitis is an unusual postoperative complication in pediatric cardiovascular surgery, associated with high morbidity and mortality. Case reports are limited, especially in Latin America, where cardiac surgery has advanced significantly. Materials and methods. A retrospective study of mediastinitis post-cardiac surgery cases at a high-complexity center in Colombia, between January 2015 and June 2023, was conducted. A detailed description of the clinical characteristics and therapeutic approaches was provided. Results. A population of 16 children with mediastinitis was characterized, predominantly male (68.7%); 62.5% were aged 1–3 months. The most common defects were transposition of the great arteries and univentricular heart. Gram-negative bacteria (37.5%) were the most common isolates, followed by gram-positive bacteria (25%). Vacuum-assisted closure (VAC) was required in 43.7% of cases. Conclusion. Advances in congenital heart disease management have led to complications such as mediastinitis, prompting the development of therapeutic strategies that would benefit from better characterization in high-complexity centers to improve outcomes.